2019
DOI: 10.1021/acsmacrolett.9b00293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Network Architecture and Linker Polarity on Ion Aggregation and Conductivity in Precise Polymerized Ionic Liquids

Abstract: Four polymerized ionic liquids (PILs) were systematically designed to study the effect of polymer architecture and linker polarity on ion aggregation and transport. Specifically, linear and network PILs with the same ammonium cations (Am) and bis­(trifluoromethane)­sulfonimide (TFSI) anions were prepared by step-growth polymerization, and polarity was tuned by incorporating two precise linkers, either polar tetra­(ethylene oxide) (4EO) linker or nonpolar undecyl (C11) linker. The glass transition temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 56 publications
(91 reference statements)
1
53
0
Order By: Relevance
“…glass transition temperature (Tg), as well as an increased conductivity for the polar EO-containing materials. 49 Furthermore, in a recent study by Polgar and co-workers on Diels-Alder-based CANs, polarity induced effects as a result of introduced acetate groups were shown to affect cluster formation within the material. 50 Also in recent work on vitrimer-like anilinium salt CANs, solvation effects as a result of polar groups have been proposed.…”
Section: A Laboratory Of Organic Chemistry Wageningen University Smentioning
confidence: 99%
See 1 more Smart Citation
“…glass transition temperature (Tg), as well as an increased conductivity for the polar EO-containing materials. 49 Furthermore, in a recent study by Polgar and co-workers on Diels-Alder-based CANs, polarity induced effects as a result of introduced acetate groups were shown to affect cluster formation within the material. 50 Also in recent work on vitrimer-like anilinium salt CANs, solvation effects as a result of polar groups have been proposed.…”
Section: A Laboratory Of Organic Chemistry Wageningen University Smentioning
confidence: 99%
“…36,[43][44][45][46][47] One factor that is however mainly overlooked when it comes to these ether moieties is the concomitant induced polar effect on the polymer network (dynamics), which was previously reported for materials that rely on ion transport. 48,49 For example in the study by Zhao and co-workers, the differences between polar EO linkers and apolar alkyl linkers were noticeable as a significant decrease in the…”
Section: Introductionmentioning
confidence: 99%
“…72 Other studies reported that ion aggregation could be enhanced by crosslinking or reducing backbone polarity, whereas plasticization led to ion dissociation. 73,74 With the large variety of ionic motifs and their controlled distribution along polymer chains, a broad range of ionic interaction energies can be achieved.…”
Section: Polymer Chemistrymentioning
confidence: 99%
“…Polymer networks containing ionic species have received attention as functional materials in liquid/gas separations, [9][10][11][12][13][14][15] soft actuators, [16][17][18][19][20] ion exchange membranes, [21][22][23][24][25] and electrolytes for energy storage. [26][27][28][29][30][31][32][33][34][35] In the context of lithium conduction, polyethylene oxide (PEO) networks with added lithium salts have been investigated and it was shown that covalent crosslinking can significantly reduce the crystallinity and increase the ionic conductivity. [36][37][38] Dual ion-conducting electrolytes based on acrylates, [27] polyethylene, [28] polyacrylonitrile, [39] epoxy, [40] and PEO networks [41][42][43] with Li salts have also been investigated, and they often show dendrite suppression capabilities when cycled with a Li electrode.…”
Section: Introductionmentioning
confidence: 99%
“…High T g PILs have greater mechanical stability but lower ionic conductivity due to lower segmental mobility. [57] Many groups have noted the important roles of polarity, ion concentration, polymer morphology, and segmental dynamics on conductivity in linear single-ion conducting systems.. [21,[57][58][59][60] Prior works on single anion conducting network polymers have investigated the roles of network versus linear architecture, [35] precise length of carbon spacers between network junctions, [61] crosslinking density, [16,62,63] ionic interactions, [55,63,64] and ion concentration [55] on ion transport through changes in T g and mechanical properties. However, there is still a need for systematic studies of Li + single-ion conducting networks with controlled architecture, charge density, and mechanical properties to understand how performance is related to molecular structure.…”
Section: Introductionmentioning
confidence: 99%